MiR-34a induces neutrophil apoptosis by regulating Cdc42-WASP-Arp2/3 pathway-mediated F-actin remodeling and ROS production. (31st December 2022) - Cao, Meiwan; Peng, Baoling; Chen, Huan; Yang, Min; Chen, Peiyu; Ye, Liping; Wang, Hongli; Ren, Lu; Xie, Jing; Zhu, Jingnan; Xu, Xiangye; Xu, Wanfu; et al.
ABSTRACT: Background: The number of neutrophils is significantly reduced in myelodysplastic syndrome (MDS), but the molecular basis remains unclear. We recently found that miR-34a was significantly increased in MDS neutrophils. Therefore, this study aims to clarify the effects of aberrant miR-34a expression on neutrophil counts. Methods: miR-34a mimics/inhibitor transfection were performed in neutrophil-like differentiated HL60 (dHL60) cells, and a FACSCalibur flow cytometer was used to measure ROS production and apoptosis. In addition, the Cdc42-WASP-Arp2/3 pathway inhibitor (ML141) and activator (CN02) treated the dHL60 cells, and then ROS production, apoptosis and related proteins expression were detected. And, luciferase reporter assay to verify the relationship of miR-34a and the Cdc42-WASP-Arp2/3 pathway. Results: overexpression of miR-34a could induce ROS production and apoptosis, decrease the expression levels of DOCK8, p-WASP, WASP, Arp2, Arp3, and increase F-actin's expression. Meanwhile, knockdown of miR-34a could decrease ROS production and apoptosis, increase the expression of DOCK8, p-WASP, WASP, Arp2, Arp3, and decrease F-actin's expression. Immunofluorescence staining showed aberrant miR-34a and Cdc42-WASP-Arp2/3 pathway could induce F-actin membrane transfer. Luciferase reporter assay indicated that DOCK8 was a direct target gene of miR-34a. Conclusion: These data indicates miR-34a may induce neutrophil apoptosis by regulating Cdc42-WASP-Arp2/3 pathway-mediated F-actin remodeling and ROS production.